Marital Satisfaction and Father Involvement on Company X's Employees: The Role of Workplace Flexibility - Somantri, Siti Dara Futri; Riasnugrahani, Missiliana; Setiawan, Tery (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
Father involvement has a positive impact on children's cognitive, emotional and social development. However, the level of this involvement is low in the Asian context, particularly in Indonesia, where traditional gender roles often reduce paternal involvement. The role of fathers in children's development is increasingly recognized, but there remains a research gap in understanding how factors such as marital satisfaction and workplace flexibility jointly influence fathers' involvement. This research aims to determine the moderating role of workplace flexibility on the relationship between marital satisfaction and father involvement with surveyed fathers who work at Company